Inhibitory effect of a cholecystokinin antagonist on the proliferative response of the pancreas to pancreatobiliary diversion. Issue 9 (September 1991) - Watanapa, P; Efa, E F; Beardshall, K; Calam, J; Sarraf, C E; Alison, M R; Williamson, R C
Abstract : Since pancreatobiliary diversion probably stimulates pancreatic growth by increasing cholecystokinin secretion, the effect of the cholecystokinin antagonist CR-1409 on this adaptive response was tested. Male Wistar rats (n = 108) weighing 220-250g were randomised to receive either pancreatobiliary diversion (n = 60) or sham diversion (n = 48) and thereafter to receive either saline injections or CR-1409 (10 mg/kg/day, subcutaneously). Rats were killed at four, seven, and 14 days postoperatively, when blood was obtained for cholecystokinin assay and the pancreas was assessed for proliferative activity by three techniques: nucleic acid and protein assay, bromodeoxyuridine labelling, and metaphase arrest after vincristine administration (1 mg/kg, intraperitoneally). Pancreatobiliary diversion increased plasma cholecystokinin concentrations by 91% at seven days and 137% at 14 days, irrespective of CR-1409 treatment. Total pancreatic RNA content was doubled by pancreatobiliary diversion at four days (2.15 v 1.07 mg/100 g body weight: p less than 0.001) and at seven days (3.43 v 1.76 mg/100 g: p less than 0.001), and trebled at 14 days (4.27 v 1.32 mg/100 g: p less than 0.001). Pancreatobiliary diversion increased bromodeoxyuridine labelling index from 1.1 to 3.7% at seven days and the cell birth rate from 0.09 to 0.06%. CR-1409 completely abolished this proliferative response and partly prevented the rise in RNA. The results confirm pancreatic hypertrophy and increased acinar cell proliferation after pancreatobiliary diversion. CR-1409 prevents this adaptive growth, probably by blocking cholecystokinin receptors. Bromodeoxyuridine labelling and the metaphase arrest technique may be used to assess pancreatic cell kinetics.